Papillary Carcinoma of Thyroglossal Duct Cyst- A Diagnostic and Therapeutic Conundrum - Agrawal, V; Colbert, KR; Kumar, S; Dharanya; Bhat, RV (Kathmandu University Medical Journal, 2023)
Thyroglossal duct cysts (TGDC) are the most common congenital midline neck mass. It accounts for 70% of congenital neck masses in children and 7% in the general population. Untreated, Thyroglossal duct cyst may transform into a thyroid carcinoma in less than 1% of cases. A 47 year old female patient presented with complaints of swelling on the anterior aspect of neck for 1 year which was progressively increasing in size. Smears from needle aspiration revealed features suspicious of Papillary carcinoma of thyroid which was confirmed as on histopathology. Thyroid gland and the adjacent lymph nodes were free of the tumour on Computed Tomography (CT). Thyroglossal duct cysts undergoing neoplastic change is more common among women. Though sistrunk’s procedure is widely accepted as a primary management, the role of total thyroidectomy with radioiodine therapy still remains a controversy due to contrasting opinions available in the literature.